Injury prevention programs against distracted driving among students. Issue 1 (July 2016) - Joseph, Bellal; Haider, Ansab; Hassan, Ahmed; Kulvatunyou, Narong; Bains, Sandeep; Tang, Andrew; Zangbar, Bardiya; O'Keeffe, Terence; Vercruysse, Gary; Gries, Lynn; Rhee, Peter
Abstract : BACKGROUND: Motor vehicle crashes are the leading cause of death and nonfatal injury among young adults. The aims of this study were to assess the magnitude of distracted driving (DD) among students and to examine the effectiveness of awareness campaign against DD. We hypothesized that DD is prevalent among students and educational efforts such as DD awareness campaign can effectively reduce it. METHODS: This study was conducted within the University of Arizona that has a student enrollment of 42, 000 students. We conducted our prospective interventional study in four phases at the university campus. Phase 1 involved 1-week preintervention observation, Phase 2 involved 1-week intervention, Phase 3 involved 1-week postintervention observation, and Phase 4 involved 1-week 6-month postintervention observation. We used a combination of e-mails, pamphlets, interactive sessions, and banners as intervention tools in student union. Our primary outcome was the prevalence of DD before, after, and 6 months after intervention. RESULTS: A total of 47, 764 observations (before, 14, 844; after, 17, 939; 6 months after, 14, 981) were performed. During the study period, overall rate of DD rate among the students was 8.8 (5.4) per 100 drivers (texting, 4.8 [3.7] per 100 drivers; talking, 3.9 [2.0] per 100 drivers). The baseline rate of DD among students during the phase one was 9.0 (1.2) per 100 drivers (texting, 4.8 [1.7] per 100 drivers; talking, 4.1 [1.1] per 100 drivers). Following intervention, there was a 32% significant reduction in overall DD (9.0 [1.2] vs. 6.1 [1.7], p < 0.001) in the immediate postintervention phase; however, the rate of DD returned to baseline at 6 months after intervention and trended toward increase (9.0 [1.2] vs. 11.1 [8.4], p = 0.34). CONCLUSION: DD is prevalent among university students. Following a comprehensive preventive campaign against DD, there was a 32% reduction in the rate of DD in the immediate postintervention period. However, a single episode of intervention did not have a sustainable preventive effect on the DD, and the rate increased to the baseline at 6-month follow-up. Targeting DD with a successful injury prevention campaign with repeated boosters may decrease its prevalence among the students.